Lung cancer associated with cystic airspaces: current progress and future perspectives - Wang, Jiarui; Dai, Jie (Oncology Reviews, 2025)
Lung cancer associated with cystic airspaces (LCCAs) is a distinct subtype of lung cancer defined by its unique radiological characteristics. It is increasing in prevalence but is often misdiagnosed. The constantly emerging radiological classification systems help characterize LCCAs and guide certain treatment methods. Compared to non-LCCAs, LCCAs are more likely to be associated with an invasive nature. The natural progression of LCCAs involves the thickening of cyst walls and the emergence of solid nodules, which are indicative of tumor progression. Despite their aggressive features, the overall prognosis of LCCAs was similar to non-LCCAs this review, we aim to systematically address the current understanding of LCCAs, including the epidemiology, radiologic classification, pathology, molecular characteristics, disease progression, and survival prognosis, highlighting the need for further research to standardize the diagnosis and treatment of LCCAs and to better understand their mechanisms of development.